2023
DOI: 10.1002/ecs2.4658
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersal effectiveness in fragmented and defaunated landscapes

Jose M. Fedriani,
Thorsten Wiegand,
Pedro J. Garrote
et al.

Abstract: Landscape fragmentation and defaunation have major impacts on plant dispersal and dynamics. However, whether the impact of such perturbations on seed dispersal and recruitment change in sign and strength across habitats and spatial scales, and whether they amplify or buffer each other, remains largely unknown. To evaluate, for the first time, the joint impact of fragmentation and defaunation on seed dispersal effectiveness (SDE) across spatial scales (e.g., short‐ and long‐distance seed dispersal), we utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 75 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…Although badgers in Matasgordas may partly compensate for the lack of fox seed dispersal, they are unlikely to fully replace them due to interspecific carnivore differences in patterns of habitat use and fecal marking behavior 63 . Seed dispersal limitation in Matasgordas likely contributes to the low local Iberian pear recruitment and adult aggregated pattern observed 8 . Indeed, field studies have indicated that this population exhibits very limited reproductive and regenerative capacity, featuring a skewed demographic structure with the majority of individuals in older age classes, few juveniles, and even fewer seedlings and saplings 64 .…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Although badgers in Matasgordas may partly compensate for the lack of fox seed dispersal, they are unlikely to fully replace them due to interspecific carnivore differences in patterns of habitat use and fecal marking behavior 63 . Seed dispersal limitation in Matasgordas likely contributes to the low local Iberian pear recruitment and adult aggregated pattern observed 8 . Indeed, field studies have indicated that this population exhibits very limited reproductive and regenerative capacity, featuring a skewed demographic structure with the majority of individuals in older age classes, few juveniles, and even fewer seedlings and saplings 64 .…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, field studies have indicated that this population exhibits very limited reproductive and regenerative capacity, featuring a skewed demographic structure with the majority of individuals in older age classes, few juveniles, and even fewer seedlings and saplings 64 . Nonetheless, other factors, such as the overabundance of seedling predators (i.e., ungulates) and summer droughts, likely also contribute to this situation 8 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations